Challenging voices: Mixed evidence for context-specific control adjustments in the auditory domain. Issue 10 (October 2020) - Berger, Anja; Dolk, Thomas; Bogon, Johanna; Dreisbach, Gesine
The flexible adjustment to changing demands is an astonishing human ability. One related phenomenon is the context-specific proportion congruency (CSPC) effect. Regarding response conflict, the CSPC refers to reduced response interference in contexts with a high conflict proportion as opposed to contexts with a low conflict proportion. Derived from previous research showing CSPCs in the visual domain, we here aim to investigate whether human voices (male vs. female) as auditory contexts trigger control adjustments. To this end, we used a numerical judgement task with number words spoken by a male or female voice. We created response conflict by presenting the words either to the left or right ear (Experiment 1), and we created different levels of processing fluency by presenting them clearly or with background noise (Experiment 2). For a given participant, either the female or the male voice was associated with a high proportion of incongruent/disfluent trials and a low proportion of congruent/fluent trials, respectively. Extending previous findings from the visual modality, we found that the frequency of challenging information within one auditory context (i.e., the voice) can lead to typical CSPC patterns. In two further experiments, using frequency biased and unbiased items, we found evidence for the contribution of associative learning. Limitations of context control associations will be discussed.